TINGKAT KEBISINGAN LALU LINTAS DAN TINGKAT KELUHAN MASYARAKAT DI DESA SIDOMULYO KECAMATAN KRlAN KABUPATEN SIDOARJO TAHUN 2014 - Ruly Hariyanti; Imam Thohari; Rachmaniyah . (Poltekkes Kemenkes Surabaya, 2014)
Road traffic is the main source of noise that disturb most urban communities. One source oftraffic noise is exhaust pipes of motor vehicles.This study was concentrated on RT 02 and RT 03 (RW 02) and RT 01 and RT 03 (RW 03) atSidomulyo village Krian district Sidoarjo regency. The aims of this study were measuring traffic noiseintensity, Identifing public complaints (such as: physiological disturbances, psychological disorders andcommunication disorders) against noise, and analyzing the effect of traffic noise on public complaints levelalong the Soenandar Priyo Sudarmo street. The sample included housewives who stayed at home almostall day long and their age are under 55 years old. The total sample to be studied was 174 respondents. Inthis descriptive study the samples were drawn by simple stratified sampling.Researchindicated that the lowest noise was in the evening at 28 meters distance from the sideof the road that was 70 dB( A).The highest noise level was acquired a house located 3.5 meters from theroadside that was 81.3 dB(A). Among the 174 respondents interviewed the study discovered 174complaints. These complaints as expressed by 174 respondents were as follow ,91 people or 52.30 %expressed heavy complaints as they experienced it and 35 people or 20.1% have light complaintsexperienced.Conclusions drawn from these studies included the facts that noise caused some forms ofcomplaints such as physiological disturbances, psychological disorders and communication disorders. Thenoise level measured along the Soenandar Priyo Sudarmo street was in violation of the standard applicableto residential areas as suggested by Indonesian Health Ministry decree, KepMenKes RI No.829/MENKES/SK/VII/1999, that it should not exceed 55 d8(A). The study suggested that people livingalong the side of a highway fumish their homes with some kinds of noise silencer to reduce the noisegenerated by motor vehicles passing through that particular street